The relationship between baseline and physical performance screening tests, and game performance outcomes in elite youth basketball - Dayson, M. (University of Kent, 2020)
Introduction: To date, limited research has examined the relationships between baseline (Range of Movement tests active, passive and loaded) and physical performance screening tests and game performance outcomes in elite youth basketball. Therefore, the experimental hypothesis for this thesis was that useful screening tests would correlate with selected game performance metrics. In addition to this, categorical data and injury correlations were considered. Tests were grouped according to their type (baseline, neuromuscular, upper limb, strength and endurance, speed and agility and jumps). The grouping allowed a clearer observation of the link between tests and game performance outcomes. The hypothesis for each group is that some tests would correlate to some game's performance outcomes. One example of this is that jump tests would correlate with both defensive and offensive rebounds. This exploratory study was primarily conducted to inform practice within elite academy basketball settings from a physiotherapy practice perspective. Method: 19 elite youth male basketball players (Mean age = 17 years; range 16-19 years) performed a series of baseline range of movement and physical performance tests divided across three sessions. Baseline testing included passive and active range of movement at the ankle, hip and shoulder. Physical tests included upper limb stability and strength, vertical jumps, reactive and non-reactive agility, lower limb balance and neuromuscular control, speed tests and strength endurance tests of hamstring and core. Results: A series of moderate and strong correlations were found between baseline range of movement (ROM), physical performance tests and some game statistic outcomes. Strongest correlations were found between offensive rebounds and shoulder passive internal rotation (Left r = .57, p < 0.01, Right r = .66, p < 0.01). Right hip passive internal rotation and free throw percentage (r = -.61 p < 0.01). Straight leg raise and free throws made (Right r = .74, p < 0.01, Left r = .62, p < 0.01). Straight leg raise and free throws season percentage (Right r = .65, p < 0.01). = r = -.56, p < 0.05, Left r = .52, p < 0.05). Right hamstring 90/90 correlated with free throws made (r = -.66, p < 0.01. Left hamstring 90/90 correlated with assists season average 9 r = -.66, p < 0.01). Left dorsiflexion with assists season average (r = -.61, p < 0.01). Right dorsiflexion passive correlated with 2 pt field goal percentage (r = -.62, p < 0.01) and defensive rebounds (r = -.64, p < 0.01). Qualitative assessment single leg squat correlated with Free throws made (Left r = .62, p < 0.01, Right .51, p < 0.05) and offensive rebounds (Left r = .61, p < 0.01, Right r = .47, p < 0.05). Side plank left correlated with defensive rebounds (r = -.70, p < 0.01). Closed kinetic chain upper extremity stability test (CKCUEST) correlated with with assists season average (r = -.72, p < 0.01). Agility T-Test correlated with number of games played season (r = -.62, p < 0.01), defensive rebound (r = -.64, p < 0.01) and total points season average (r = -.66, p < 0.01). No significant correlation was found between baseline testing and injuries Discussion: The findings of the present study suggest that some baseline range of movement (ROM) and physical performance tests correlate with game performance outcomes in elite youth basketball. Understanding and interpreting the data and progressing testing protocols to fully integrate elements of sport specific movement and analysis is key to developing protocols that ultimately have a bearing on their relationship to game performance. The findings will have direct implication on applied practice as these results are used to adapt interventions and develop further testing. Conclusion: Multiple correlations were found between baseline range of movement (ROM) and physical performance tests with season long game statistics. The findings from the present study can be used to elicit changes in practice so as to ensure tests provide information for performance as oppose to just baseline data for comparison.